Group of Least Developed Countries position paper (UN New YorkUS, 2011)
Aligns with the contents of the position paper of the Group of 77 and China, and makes some addditional points that need to be particularly focussed from the LDCs perspectives. Outlines the expectations of the group. Identifies eight priority areas for action.
Keywords: LEAST DEVELOPED COUNTRIES